Analisis Manajemen Risiko Pada Usaha Tani Kopi Sukahurip Untuk Meningkatkan Keberlanjutan Produksi - Fidelairna Daniswara; Dena Destiani; Syahira Rachmadina; Listi Sinta Nur Oktaviani; Alfiana (Indo Publishing, 2025)
This study aims to analyze risk management in the Sukahurip Coffee Farming Enterprise as an effort to enhance production sustainability through the ISO 31000 approach. In accordance with the concept of risk management proposed by Susanto & Meiryani (2018) and the guidelines for risk identification by Kountur (2008), this research employs a qualitative descriptive method through observations and in-depth interviews to describe actual conditions in the field. The risks analyzed focus on six main categories: operational, financial, marketing, market, human resources, and legal. The findings indicate that the most critical risks lie in the operational aspect, particularly unpredictable weather and seasonal harvesting, which fall into the extreme and high-risk categories. Financial and market risks are at a moderate level due to price fluctuations and limited market data, while legal risks are relatively low because the enterprise operates under the supervision of the plantation office. Based on the 5×5 risk matrix, most risks can be mitigated through improvements in standard operating procedures (SOPs), market diversification, enhancement of human resource capacity, and internal quality monitoring. These findings underscore the importance of implementing structured risk management to maintain production stability and strengthen the competitiveness of local coffee farming enterprises.